2015
DOI: 10.1016/j.algal.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Production of fucoxanthin-rich fraction (FxRF) from a diatom, Chaetoceros calcitrans (Paulsen) Takano 1968

Abstract: Fucoxanthin is the major carotenoid produced by diatoms and shown to exhibit potent anti-obesity and anticancer activities. This study presents a simple protocol for the preparation of fucoxanthin-rich fraction (FxRF) with high antioxidative properties from a selected marine diatom, Chaetoceros calcitrans. Fucoxanthin concentrates were prepared from crude methanolic extract (CME) with liquid-liquid partitioning of three types of solvent systems (i.e. diethyl ether-water, dichloromethane-water and ethyl acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…The structure of fucoxanthin includes a usual allenic bond and 5, 6‐monoepoxide in its molecule, and almost all of them were trans ‐fucoxanthin in brown algae (Jaswir et al ., ). Fucoxanthin was also responsible for antioxidant activity of algal extracts reported by several researchers (Fung et al ., ; Foo et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The structure of fucoxanthin includes a usual allenic bond and 5, 6‐monoepoxide in its molecule, and almost all of them were trans ‐fucoxanthin in brown algae (Jaswir et al ., ). Fucoxanthin was also responsible for antioxidant activity of algal extracts reported by several researchers (Fung et al ., ; Foo et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…; Foo et al . ,b, ,b). The aforementioned pigments are closely related to one another; thus, they exhibit many of the functional metabolic and physiological characteristics of carotenoids (Guerin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids such as astaxanthin are known for their metal‐chelating properties (Polyakov, Focsan, Bowman, and Kispert, ). Studies on the iron‐chelating activity of fucoxanthin‐containing extracts are available in the literature (Budhiyanti, Raharjo, Marseno, & Lelana, ; Foo et al, ). These studies found a similar high iron‐chelating activity to that reported in the present study.…”
Section: Resultsmentioning
confidence: 99%